Hostage-taking 1754: Virginians vs Canadians - Steele, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2005)
AbstractWhen Virginians, Canadians, and Indians clashed, the Allegheny borderlands were a new ‘muddle ground’ of fateful cultural confusions rather than an established middle ground of recognized compromises. The taking of captives was an early, significant, and portentious part of the contest. Indians who were resettling the region were familiar with traditional panis slavery, with raiding for captives in long-range blood feuds, and with trading Indian captives to Europeans. Their capture of European traders, as diplomatic gifts, was a very recent development.Colonial trade rivalries became military, and the paltry forts became sites of negotiated surrender in 1754. Before European regulars arrived in numbers, or the Anglo-French war was formally declared, colonial intruders surrendered to their Indian and colonial rivals on three occasions. Virginians surrendered their incomplete stockade at the forks of the Ohio in April. In May, Virginians and Indians ambushed a Canadian party under Ensign Jumonville, and survivors of the initial skirmish sought quarter. Within five weeks, avenging Canadians and Indians forced Virginians to surrender their aptly-named Fort Necessity.In taking prisoners and hostages in the Allegheny borderlands, colonial officers adapted and violated both European and Indian conventions, and took different approaches in dealing with the independent actions of their Indian allies. On the eve of a major war, captives and their brethren learned what distinctions had been made, and that they might well be violated.